An analysis of equity share price movement of selected companies listed in nse - R, CHITRA; M, SATHYA (Journal of Management and Science, 2012)
The stock market has an important role in the allocation of resources, both directly as a source of funds and as a determinant of firm’s value and borrowing capacity. This study we made a study and analysis on Equity share price behaviour of selected companies listed in NSE India. The Purpose of the study is, attempted to test the equity price movements of IT,Pharmaceuticals, Banking and Automobiles sectors. These are taken as sample sectors. The objective of the study is to analyze the Equity share price movement of selected companies listed in NSE, India and to analyze the movements of the high pricedequity shares of four sectors for the past 3 years. Data collections are to be used in the study is secondary data. The study usestools such as Simple Moving Average, Rate of Change, Relative Strength Index, Stochastic oscillator and Trend analysis. TheMonthly share prices of above mentioned companies were taken for a period of three years from January 2009 to Dec 2011. Theclosing prices of share prices were taken. All four sectors registered tremendous growth in the past 3 years, and as per theanalysis all these sectors companies were predicted as best to invest for better rate of return for the investors.